THE PANDEMİC'S IMPACT ON DEBT LEVELS IN DEVELOPİNG COUNTRİES (Third Sector Social Economic Review, 2024)
In the global economic system, mechanisms of 'credit,' and consequently, the significance of 'indebtedness,' hold great importance. Today, a significant portion of countries worldwide, regardless of being developed or developing, carry a serious burden of debt. However, the indebtedness of developing countries creates a more distinct economic vulnerability compared to developed countries. This study focuses on the changes in the levels of indebtedness of developing countries with similar economic structures during the pandemic period. Countries such as Brazil, China, Russia, India, Indonesia, Mexico, Russia, Turkey, and South Africa are discussed. It is observed that the indebtedness levels of these countries have significantly increased during the pandemic. If these countries cannot find future sources of financing, they may face the risk of being unable to repay their debts. There is an evaluation that suggests the need to restructure the debt management policies of these countries, the requirement for international institutions to provide incentives to developing countries, and the necessity for reforms in fiscal policies.
Keywords: Developing Countries; Debt; Pandemic; Crisis; Default